2013
DOI: 10.21512/comtech.v4i2.2611
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Pembelajaran Algoritma Dasar Interaktif Berbasiskan Computer Assisted Instruction

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…After that, it gives recommendation to instructors and learners so they can take actions immediately to prevent failure (Yulianto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After that, it gives recommendation to instructors and learners so they can take actions immediately to prevent failure (Yulianto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches shown that there are several educational tools to support students in starting learning programming (Yulianto et al, 2013). All are operated in offline, online, or both ways (Brandão et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Things to be considered in the use of animation is a memory processing capabilities, knowledge of the early disciplines, spatial ability, and how animations were created. Good animation can support students to form a mental picture of the processes that occurs and requires more effort to be learned (Yulianto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%